DUAL EDUCATION - TOOL FOR RECONSIDERING EDUCATION - BARBĂNEAGRĂ OXANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
The scientific approach of this paper addresses the problem of the imbalance in the labor market between the educational offer and the labor force demand. One of the problems that led to the imbalance on the labor market and the labor shortage is conditioned by the weak interaction between the professional training system and the actors involved in the hiring process. Under these conditions, we consider that professional education in the dual system becomes a very important mechanism.This allowed the author to analyze the model of dual education at the national level but also the experience of other countries.